Performance of Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae) on eggs of Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) - Laurentis, Valéria Lucas [UNESP]; Ramalho, Dagmara Gomes; Santos, Nathália Alves; Carvalho, Vanessa Fabíola Pereira [UNESP]; Vacari, Alessandra Marieli; De Bortoli, Sergio Antonio [UNESP]; Veneziani, Rodrigo Cassio Sola; da Costa Inácio, Gabriel; Dami, Bruno Gomes (Springer Nature, 2019)
Helicoverpa armigera (Hübner) (Lepidoptera: Noctuidae) is a polyphagous pest with a wide geographic distribution. This pest first arrived in Brazil in 2013, and since then studies on possible control methods for it have been necessary. A possible method for the control of H. armigera is using the egg parasitoid Trichogramma pretiosum Riley (Hymenoptera: Trichogrammatidae). Therefore, the objective of this study was to evaluate the performance of T. pretiosum on H. armigera eggs, which are known to represent suitable hosts for the development of this parasitoid species in the laboratory. Parasitism and emergence rates and the duration of the egg-to-adult period of T. pretiosum were investigated following 24- and 48-h exposures of this parasitoid to H. armigera and Corcyra cephalonica (Stainton) (Lepidoptera: Pyralidae) eggs. The longevity of offspring after the 24-h exposure was studied, as well as the frequency of parasitism and emergence, host preference, and the emergence of offspring from eggs of different ages or oviposited by lepidopterans on different days. Parasitism was 14.4 and 34.9% more frequent on C. cephalonica than on H. armigera after 24 and 48 h of exposure, respectively. In C. cephalonica, parasitism was 27.2% higher after 48 h. Parasitism was more frequent on C. cephalonica eggs collected on the second day of oviposition (76.2%), and on H. armigera on the third day of oviposition (71.1%). Parasitism frequency was lower on 2-day-old C. cephalonica eggs (63.3%) and on 3-day-old H. armigera eggs (41.3%). When tested with a chance of choice between hosts, T. pretiosum preferred H. armigera, while in the test with no chance of choice there was no difference in preference. Thus, T. pretiosum may be considered a tool for the Integrated Pest Management (IPM) of H. armigera.